SOLID CaCO3 FORMATION IN WATERS OF CIRCULATING COOLING SYSTEMS OF POWER PLANTS UNDER THE CONDITIONS OF ELECTRIC LOAD CHANGE - Kochmarskii, V. Z.; Melnyk, V. O. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2018)
The rate of solid calcium carbonate (Dve) formation in circulating water (CW) of circulating cooling systems (CCS) of power plants with cooler towers and the stability index of such water at changing electric load is analyzed. The relationship between streams of CCS, namely, feeding, evaporation and blow, which exist under the condition of constant CCS water volume and dependence of evaporation flow upon units load are the basis of analysis. Such dependence is based on the fact that the main channel of heat dissipation after steam turbine units is evaporation in cooling towers. The general expression has been obtained in quasiequilibrium approximation that establishes the relation between Dve and CW stability index. This dependence allows calculating CW stability degree for any models of CaCO3 formation kinetics and to obtain corresponding Dve value. It has been shown that the rate of solid CaCO3 formation is directly proportional to electrical load of power plant, Ca2+ ion concentration in feed water and fraction of used heat dissipated by evaporation, antiproportional to stability index, inverse to CCS water volume and the average efficiency of power plant.